The abrogation of the HOXB7/PBX2 complex induces apoptosis in melanoma through the miR‐221&222‐c‐FOS pathway. Issue 4 (13th March 2013) - Errico, M. Cristina; Felicetti, Federica; Bottero, Lisabianca; Mattia, Gianfranco; Boe, Alessandra; Felli, Nadia; Petrini, Marina; Bellenghi, Maria; Pandha, Hardev S.; Calvaruso, Marco; Tripodo, Claudio; Colombo, Mario P.; et al.
<x xml:space="preserve">Abstract</x> Cutaneous melanoma is the fastest increasing cancer worldwide. Although several molecular abnormalities have been associated with melanoma progression, the underlying mechanisms are still largely unknown and few targeted therapies are under evaluation. Here we show that the HOXB7/PBX2 dimer acts as a positive transcriptional regulator of the oncogenic microRNA‐221 and ‐222. In addition, demonstrating c‐FOS as a direct target of miR‐221&222, we identify a HOXB7/PBX2→miR‐221&222 →c‐FOS regulatory link, whereby the abrogation of functional HOXB7/PBX2 dimers leads to reduced miR‐221&222 transcription and elevated c‐FOS expression with consequent cell death. Taking advantage of the treatment with the peptide HXR9, an antagonist of HOX/PBX dimerization, we recognize miR‐221&222 as effectors of its action, in turn confirming the HXR9 efficacy in the treatment of human melanoma malignancy, whilst sparing normal human melanocytes. Our findings, besides suggesting the potential therapeutic of HXR9 or its derivatives in malignant melanoma, suggest the disruption of the HOXB7/PBX2 complexes, miR‐221&222 inhibition or even better their combination, as innovative therapeutic approaches.